Factors Impacting on SMEs Internationalization: Dairy Industry in Zimbabwe - Mpofu, Tongesai; Sauti, Joyline (International Journal of Business, Economics and Management, 2014)
The main thrust of the study was to identify and assess the factors that impact on Small to Medium Enterprises (SMEs) internationalization in the Zimbabwean dairy industry. The objectives of the research are to identify the factors that drive or motivate the internationalization of SMEs, analyze most significant barriers to SME internationalization, examine the strategies being adopted by SMEs in their internationalization process and identify and recommend strategies that will assist SMEs in dairy sector internationalization. Companies internationalize because of many factors that include profit motives, costs minimization, diversification of the markets, search for new opportunities and saturated domestic market. The factors considered in internationalization include the knowledge on the market, the availability of resources, the strategies to be used and the market environment. Despite the main motives of companies to internationalize and the advantages involved, there are obstacles that the company must overcome for successful internationalization. The sample for the study was eight SMEs in the dairy industry and simple random sampling was used for selecting respondents. Questionnaires and face to face interviews were used for data collection. The study found that the major drivers for internationalization in the Zimbabwean dairy industry included the drive to gain a large market share, maximize profits, expansion, managerial urge and competitive pressure. The dairy SMES face operational, informational, environmental and marketing challenges. The internationalization strategies used in the dairy sector include importing, exporting, foreign collaborations and subsidiaries. The study recommends that there has to be openness to internationalization, financial incentives and assistance should be given to internationalizing SMEs and there must be provision of business support service.